Power outage and environmental justice in Winter Storm Uri: an analytical workflow based on nighttime light remote sensing - Xu, Jinwen; Qiang, Yi; Cai, Heng; Zou, Lei (International journal of digital earth, 2023)
The intensity of extreme weather events has been increasing, posing a unique threat to society and highlighting the importance of our electrical power system, a key component in our infrastructure. In severe weather events, quickly identifying power outage impact zones and affected communities is crucial for informed disaster response. However, a lack of household-level power outage data impedes timely and precise assessments. To address these challenges, we introduced an analytical workflow using NASA's Black Marble daily nighttime light (NTL) images to detect power outages from the 2021 Winter Storm Uri. This workflow includes adjustments to mitigate viewing angle and snow reflection effects. Power outage is detected by comparing storm-time and baseline (normal condition) NTL images using an empirical adjusted equation. The outcomes of the workflow are 500-meter resolution power outage maps, which have the optimal correlation with real outage tracking data when NTL intensity is reduced by 26%. With the resultant power outage maps, we analyzed the relations between power outages and disadvantaged populations in 126 Texas counties and 4182 census tracts to evaluate environmental justice in the storm. The results show that Latino/Hispanic communities tend to suffer more from power outages at both the county and census tract levels.